HORIZONS OF THE FUTURE science fiction, education, and utopian imagination. - Slater, Graham B. ([S.l.] : ROUTLEDGE, 2024)
Horizons of the Future: Science Fiction, Utopian Imagination, and the Politics of Education examines the relationship between science fiction, education, and social change in the 21st century. Global capitalism is ecologically unsustainable and ethically indefensible; time is running out to alter the course of history if humanity is to have hope of a livable future beyond the next century. However, alternatives are possible, offering much more equality, care, justice, joy, and hope than the established order. Popular culture and schools are key sites of struggles to imagine such alternatives. Drawing on critical theory, cultural studies, and sociology, Slater articulates the promising connection between science fiction and the future of education. He offers cutting-edge engagement with themes, perspectives, and modes of imagination in science fiction that can be mobilized politically and pedagogically to envision and enact critical forms of education that cultivate new utopian ways of relating to self, society, and the future. This thought-provoking book will be of interest to scholars and students in the social sciences and education.
Keywords: Science fiction -- History and criticism; EDUCATION / Philosophy & Social Aspects; EDUCATION / Multicultural Education; EDUCATION / Higher